Analisis Cluster Kabupaten/Kota di Jawa Timur Berdasarkan Faktor Kesejahteraan Masyarakat Tahun 2023 - Rindy Retno Prihastari; Salsabila Aulia Azizah; Sri Pingit Wulandari (Mutiara: Jurnal Ilmiah Multidisiplin Indonesia, 2024)
East Java Province is a region with significant economic contribution in Indonesia, occupying the third position nationally with a contribution of 14.26%. However, despite its rapid economic growth, East Java still faces welfare challenges, especially in terms of poverty which is still relatively high compared to other provinces on the island of Java. The poverty rate in East Java is on a downward trend, but it still remains above the national average. This condition indicates an imbalance in the welfare of the community in the East Java region. Welfare is measured based on the ability of the community to meet decent, healthy, and productive basic needs, with the Human Development Index (HDI) as one of the main indicators. HDI can measure human development achievements based on several basic components of quality of life, including the education dimension, the age and health dimension, and the standard of decent living. Therefore, the government needs to group regions with appropriate characteristics to make it easier to make policies. One of the statistical analyses that can be used in this study is cluster analysis. The results of this study are that East Java Province in 2023 shows a diversity of welfare indicators, such as TPT, HDI, and AHH, reflecting differences in economic, educational, and health conditions between regions. The cluster method with the best assessment in this study is the K-Means method with five clusters. The characteristics in clusters I and II tend to have low welfare, while clusters III, IV, and V show better welfare. The results of this study show a change in the number of clusters compared to previous research conducted by Muhammad Fikry Al Farizi et al. in 2022. The previous study produced four clusters using the average linkage method.